2020
DOI: 10.1186/s13662-020-02799-3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the delay on the p53 micronetwork

Abstract: Time delay plays a crucial role in p53 dynamic. However, the theoretical understanding is still lower. Thus we construct a micro-differential equation model and introduce the time delay τ based on the regulation process. Firstly, we linearize the system and analyze the associated characteristic equation. We can conclude that there exists the delay threshold $\tau _{0}$ τ 0 such that when the delay τ is less than $\tau _{0}$ τ 0 , the system is asymptotically stable and otherwise stable oscillations occur.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In recent years, a common extension when investigating the role of delays is to consider the extended model given in Figure 6 b. It has been shown that the delays in both negative feedback loops are important components to derive oscillatory behaviour [ 83 , 84 ]. One difficulty though is that in order to make analysis of the models tractable it has, so far, required that both delays are assumed to be equal, which may or may not be the case in the real biological system.…”
Section: Mathematical Modelling Of P53mentioning
confidence: 99%
“…In recent years, a common extension when investigating the role of delays is to consider the extended model given in Figure 6 b. It has been shown that the delays in both negative feedback loops are important components to derive oscillatory behaviour [ 83 , 84 ]. One difficulty though is that in order to make analysis of the models tractable it has, so far, required that both delays are assumed to be equal, which may or may not be the case in the real biological system.…”
Section: Mathematical Modelling Of P53mentioning
confidence: 99%
“…In the past research, great achievements have been made in establishing the stability of gene regulatory networks with time delays [10,11,12,13]. Mao et al analyzed that the time delay in the model is a necessary factor for the system to generate oscillation [14]; Xia et al pointed out that transcription delay can determine the vibration period of gene expression [15]; Wang et al found that the existence of time delay will lead to rich dynamic behavior of the system [16]. However, single time delay analysis is far from enough in gene regulation networks.…”
Section: Introductionmentioning
confidence: 99%